Obesity Paradox: Origin and best way to assess severity in patients with systolic HF. (4th September 2015) - Pozzo, Joffrey; Fournier, Pauline; Lairez, Olivier; Vervueren, Paul‐Louis; Delmas, Clement; Elbaz, Meyer; Carrie, Didier; Galinier, Michel; Roncalli, Jerome
<x xml:space="preserve">Abstract</x> Objective Obesity in patients with heart failure (HF) is a factor of better prognosis, supposedly partly because of the particular epidemiology of HF in this population. This study expected to compare the parameters of severity and mortality in patients with and without obesity, to better understand the origin of this paradox. Methods Two hundred twenty‐two patients with nonischemic HF and systolic dysfunction were divided into two groups according to their body mass index (≥30 vs. <30 kg/m2, respectively) and explored for functional parameters and prognosis. Results B‐type natriuretic peptide (BNP) levels were lower and peak oxygen consumption higher in patients with obesity. Patients with obesity had a better prognosis than patients without obesity with a 4‐year mortality of 11.1% and 26.4%, respectively (P = 0.009). By univariate analysis, obesity was associated with a reduced risk of death: HR 0.52 [0.28–0.99]. This protective effect was no longer present after adjusting for VO2max and BNP level. Conclusions The obesity paradox is probably partly due to an overestimation of the severity of HF in patients with obesity because of the multifactorial nature of their dyspnea. Obesity no longer has a protective effect after adjustment for the usual prognostic parameters of HF.